The historical collection of photographic portraits in the Archive of the Congress of Deputies (1870-1939): origin, characteristics and documentary treatment - Rodríguez Bermejo, Sandra; García Fernández, Laura; García Sánchez-Crespo, Yasmina (Revista General de Información y Documentación, 2023)
The historical collection of photographic portraits of deputies, senators, assembly members and procurators of the Archive of the Congress of Deputies is a set of nearly 4,000 photographs covering a chronological framework of approximately one hundred years, from the 1870s to the end of the period of the Spanish Cortes in 1977. The study presented below focuses on analysing the first part of the collection, up to the first third of the twentieth century, which constitutes an unpublished gallery in which not only the main protagonists of political activity at the time are represented, but also the photographic studios that made the production of these images possible, such as Kâulak, Compañy, Biedma, Alfonso and Franzen, among others. The motivation behind this is twofold: on the one hand, to make the collection known and vindicate its potential, and, on the other, to present the documentary treatment carried out on it, in which everything has been taken into account, from its material conservation to the actions linked to its dissemination.
Keywords: Photography; Photographic Portrait; Photographic Archive; Parliamentary Archive; Archive of the Congress of Deputies; Documentary Treatment; Digital Preservation; Adobe Photoshop Lightroom; Adobe Photoshop Lightroom